2014
DOI: 10.1136/annrheumdis-2014-eular.5331
|View full text |Cite
|
Sign up to set email alerts
|

SAT0233 Comparison of Abatacept and Other Biologic DMARDS for the Treatment of Rheumatoid Arthritis Patients: A Systematic Literature Review and Network Meta-Analysis: Table 1.

Abstract: Background Rheumatoid arthritis (RA) is a chronic, systemic inflammatory disorder that, if inadequately treated, often progresses to joint destruction. Currently, patients are initially treated with conventional disease- modifying anti-rheumatic drugs (DMARDs); in patients with an inadequate response (IR), biologic DMARDs are often combined with methotrexate (MTX) or other DMARDs to improve efficacy. Objectives To compare the relative efficacy and safety of abatacept versus all relevant biologic DMARDs in MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…This recommendation was based on evidence that was rated down in quality for indirectness, as no RCTs were performed in patients undergoing THA or TKA. We abstracted data from a systematic review of literature that included systematic reviews and meta‐analyses of biologic agents versus placebo (and occasionally versus control treatment including nonbiologic DMARDs) in nonsurgical patients, which revealed that the risk of serious infections was increased with biologic agents, with most odds/hazards/risk ratios ∼1.5 (range 0.61–8.87) and a higher risk of serious adverse events with most odds/hazards/risk ratios ∼1.5 (range 0.33–2.54) . Our systematic review did not provide ample evidence that would support a differential risk of serious infection among available biologic agents .…”
Section: Results/recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This recommendation was based on evidence that was rated down in quality for indirectness, as no RCTs were performed in patients undergoing THA or TKA. We abstracted data from a systematic review of literature that included systematic reviews and meta‐analyses of biologic agents versus placebo (and occasionally versus control treatment including nonbiologic DMARDs) in nonsurgical patients, which revealed that the risk of serious infections was increased with biologic agents, with most odds/hazards/risk ratios ∼1.5 (range 0.61–8.87) and a higher risk of serious adverse events with most odds/hazards/risk ratios ∼1.5 (range 0.33–2.54) . Our systematic review did not provide ample evidence that would support a differential risk of serious infection among available biologic agents .…”
Section: Results/recommendationsmentioning
confidence: 99%
“…We abstracted data from a systematic review of literature that included systematic reviews and meta‐analyses of biologic agents versus placebo (and occasionally versus control treatment including nonbiologic DMARDs) in nonsurgical patients, which revealed that the risk of serious infections was increased with biologic agents, with most odds/hazards/risk ratios ∼1.5 (range 0.61–8.87) and a higher risk of serious adverse events with most odds/hazards/risk ratios ∼1.5 (range 0.33–2.54) . Our systematic review did not provide ample evidence that would support a differential risk of serious infection among available biologic agents . Because avoiding infection was significantly more important to patients than flares in the postoperative period, the Panel did not support separating biologic agents regarding infection risk in the perioperative period until further studies clarify and establish differences in risk .…”
Section: Results/recommendationsmentioning
confidence: 99%
“…Иммуногенность под-кожной формы АБЦ не зависела от сопутствующего при-менения МТ и была сходной на фоне как монотерапии АБЦ подкожно (2%), так и комбинированной терапии АБЦ и МТ (3,9%) [27]. Завершая обсуждение основных результатов, касаю-щихся эффективности и безопасности подкожного введе-ния АБЦ при РА, следует обратить внимание на материалы недавно подготовленного систематического обзора и мета-анализа (сетевой) 21 РПКИ, посвященных сравнению эф-фективности и безопасности подкожной и внутривенной форм АБЦ и 5 ингибиторов ФНОα, моноклональных ан-тител к рецепторам ИЛ6 (тоцилизумаб -ТЦЗ), а также пе-рорального ингибитора JAK -тофацитиниба -в комбина-ции с МТ [38]. Установлено, что и подкожная, и внутри-венная формы АБЦ обладают сходной эффективностью, но безопасность (риск инфекционных осложнений, тяже-лых инфекций и тяжелых НР) был ниже на фоне подкож-ного введения АБЦ, чем других ГИБП (табл.…”
Section: иммуногенностьunclassified
“…Сравнительная эффективность и безопасность подкожной формы АБЦ по сравнению с ингибиторами ФНОα и ТЦЗ, ОШ (95% ДИ) [38] CD4+ИЛ17A в периферической крови, что коррелирова-ло с положительной динамикой индекса DAS28, умень-шением концентрации ИЛ6 и ММП3. Принимая во вни-мание, что Т рег обладают способностью дифференциро-ваться в Th17-клетки, в том числе и при участии ИЛ6, а ИЛ17 (и ИЛ6) являются мощными индукторами RANKL на остеобластах (ОБ) и синовиальных фибробла-стах, эти результаты позволяют объяснить многоплано-вый механизм действия АБЦ на синовиальное воспале-ние и костную резорбцию при РА.…”
Section: таблицаunclassified
See 1 more Smart Citation